PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM MENINGKATKAN HAFALAN JUZ 30 MELALUI METODE QIRO’ATI SISWA KELAS 5 SDIT AL-ISTIQOMAH - Rachmadewi, Zahra Aulia; Muzaki, Iqbal Amar; Ismail, Achmad Taufik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the principal's role as a supervisor in improving the quality and quantity of Juz 30 memorization through the Qiro'ati method in grade 5 at SDIT Al-Istiqomah Karawang. The core problem of this research lies in the fluctuation of students' memorization motivation and the critical need for standardizing tajwid pronunciation quality in accordance with Qiro'ati rules. The method employed in this study is a qualitative research approach with a case study design. Data collection was carried out through in-depth interviews with the school principal and tahfidz teachers, direct observation of the supervision process, and documentation of students' memorization progress books. The scientific findings indicate that the principal exercises the supervisory role through four main pillars: integrated supervision planning, clinical classroom observation using the sorogan/individual reading technique, evaluation based on progress tracking books, and follow-up guidance for teacher competency development alongside structured reward systems. The implementation of this academic supervision successfully minimized students' tajwid errors and significantly optimized the achievement percentage of Juz 30 memorization. The study concludes that consistent clinical supervision by the principal enhances the effectiveness of the Qiro'ati method and sustains teachers' Al-Qur'an instructional performance.